Islamic eating practices towards disease prevention: a comprehensive systematic review - Abdul Razak, Nadhirah; Afandi, Aflah; Mohd Abu Bakar, Wan Azdie (Kulliyyah of Allied Health Sciences, IIUM, 2024)
PURPOSE:This systematic literature review investigates the role of Islamic eating practices in disease prevention, focusing on the effects of Islamic fasting, the impacts of Islamic eating practices, and the integration of Islamic dietary principles with modern nutritional science.METHODS:A systematic search was conducted across Scopus and Web of Science databases, utilising advanced search techniques, and following the PRISMA framework. A total of 22 articles published between 2020 and 2024 were identified for inclusion.RESULTS:Numerical results reveal diverse physiological effects of Islamic fasting, including improvements in metabolic health, cardiovascular function, and immune response. Psychological and behavioural impacts such as increased mindfulness, improved self-control, and enhanced spiritual well-being are also discussed. Furthermore, the integration of Islamic dietary principles with modern nutritional science highlights the alignment between Quranic teachings and contemporary nutritional recommendations.CONCLUSION:This review underscores the multifaceted benefits of Islamic eating practices for disease prevention and emphasizes the need for further research to fully elucidate their mechanisms and potential applications in public health interventions.